The Founding of Environmental Justice Organizations Across U.S. Counties during the 1990s and 2000s: Civil Rights and Environmental Cross-Movement Effects. (30th July 2014) - Stretesky, Paul B.; Huss, Sheila; Lynch, Michael J.; Zahran, Sammy; Childs, Bob
Abstract : This research expands upon organizational ecology theory to examine variations in founding of organizations in the formalized sector of the environmental justice movement across U.S. counties for two time periods (1990—1999 and 2000—2008). Cross-movement effects are examined to determine if founding is more or less likely to occur in counties where related civil rights and environmental organizations are located. Consistent with the notion of agglomeration effects, we hypothesize that during the 1990s the relationship among civil rights density, environmental density, and environmental justice founding is positive and suggests cooperative efforts. That is, environmental justice organizations should form in counties where civil rights organizations and environmental organizations exist. Because the focus of environmental justice organizations may have expanded over time and created a more competitive atmosphere, cross-movement relationships that were positive across counties during the 1990s are hypothesized to turn negative across counties during the 2000s. Multivariate analysis suggests mixed support for these hypotheses. Specifically, civil rights density is positively associated with environmental justice founding during the 1990s and negatively associated with environmental justice founding during the 2000s—suggesting potential cooperative and then competitive effects across counties over time. However, the correlations between environmental density and environmental justice founding, while positive and statistically significant during the 1990s, are not statistically significant during the 2000s. Thus, in the case of organizations in the formalized sector of the environmental and environmental justice movements it appears that there is a trend toward competitive effects even as those effects have yet to materialize.